A Comparative Study of Educational Contracts: An Analysis of an Effective and Creative Unilateral Will in Iran and French Law - Ghasem Firozifar (Comparative Education Society of Iran ( CESIR), 2021)
Due to the shortage of manpower, many non-governmental schools in Iran have been forced to enter into educational contracts with various individuals - as temporary workers. While contracts are mostly short-lived, many employers take advantage of employees' effective and creative unilateral will by setting imposed terms. Given the importance of this issue from a legal perspective, the purpose of study is a comparative study of educational contracts with regard to the role of effective and creative unilateral will of one of the parties to the contract in the legal system of Iran and France. The method of the present study is qualitatively comparative and the documentary method was used to collect data. Findings show that in both legal systems, the creative and effective will of the parties to the contract is acceptable. Also, in France, this will is subject to the contract and consent, while in Iran, the contract is sufficient for a judge to vote. Another finding of the research reveals that when there is a dispute between the parties to the contract, in both countries, the main emphasis of the judge is to make a decision to refer to the inner will of the individual. However, in France, the obligor has the right to cancel unilateral obligations based on his creative and effective will during the term of the contract, while in the Iran’s legal system this is not possible. According these findings, it seems that the Iran legal system mainly votes in favor of educational employers. Therefore, it is suggested that the Iranian legislators - according to the economic conditions of the society and experiences of the French legal system - to amend the laws related to unilateral obligations in relationship between the employer and the educational staff.